Pendampingan anak yang memiliki kesulitan belajar “Disleksia’’ di Sekolah - Dewi Rosmawati; Y. Touvan Juni Samodra (Persatuan Guru Republik Indonesia Kota Banjarbaru, 2021)
SD Negeri 21 Jopo located in Jopo hamlet, Cupang Gading village, Sekadau upstream district, Sekadau district, 39 students, among the number of students, needs exceptional guidance. The student named Satria (12 years old) was born without a father, has a natural skin feature all over his body which is genetically from his mother, so his friends often shun his friends. Physically, he may not be too different from other students. However, physically he becomes a hyperactive person, cannot stay still, and cannot focus on learning activities, so he is far behind the lessons of his other friends. The best practice aimed to provide educational services to these students, even if only one person. The method used is by conducting special guidance activities for these students with a